Women Contributing to Food Sovereignty through Sustainable Agriculture - Santos, Esperanza “Pangging” A.; Lacanilao (SARILAYA), Margie (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia)
There is a growing consensus among advocates in the Philippines that promoting organic or ecological farming plays  a crucial role in achieving sustainable agriculture. Sustainable agriculture is considered here as a technological approach and system of  production that takes care of the needs not only of the present but also of the future generations without putting at risk the environment and people’s health. This paper presents how Sarilaya, a women’s organization, attempts to put the above concepts into practice with its sustainable agriculture project in Barangay Imelda Valley in Palayan City located within the province of Nueva Ecija in Luzon Island.
Keywords: sustainable agriculture, women’s movement, ecological farming